A prospective cohort study to determine effectiveness of cystoinflation to prevent bladder injury in women with previous caesarean section - Dwiwedi, Aparna; Dave, Anupama; Thora, Akanksha; Pandit, Meeta; Lakhra, Akansha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The rising rate of caesarean sections (C-sections) has led to an increase in associated surgical complications, particularly urinary bladder injuries in patients with dense pelvic adhesions. Repeat C-sections elevate the risk of such injuries due to adhesions between the bladder and uterus. Cystoinflation, or retrograde bladder filling with saline, has been proposed to improve visualization and reduce injury risk, but its application in C-sections is underexplored. The present study aimed to evaluate the effectiveness of intraoperative cystoinflation in reducing urinary bladder injury during C-sections in women with previous caesarean deliveries and dense pelvic adhesions. Methods: This prospective cohort study was conducted at MGM medical college and MTH hospital, Indore, over 12 months (October 2022-October 2023). A total of 240 women undergoing C-sections with dense adhesions were divided into two groups: group 1 (n=120) with cystoinflation, and group 2 (n=120) without. Primary outcome was bladder injury; secondary outcomes included blood loss; duration of surgery, complications, and hospital stay. Results: Bladder injuries occurred in 3.3% of patients in group 2 and none in group 1 (p<0.001). Urinary tract infections and micturition issues were also significantly lower in the cystoinflation group. Mean hospital stay was shorter in group 1 (4.10±0.42 days) than in group 2 (4.88±1.86 days, p<0.001). Blood loss and operative time showed non-significant trends favouring cystoinflation. Conclusions: Cystoinflation is a safe, simple, and effective technique that significantly reduces bladder injury and postoperative complications during C-sections in high-risk women. Its routine use in such cases is recommended.